PEMBERDAYAAN â€œPETANI PEREMPUAN PERKOTAANâ€ BERBASIS PADA KELUARGA SIAGA DAN MANAJEMEN EKONOMI MANDIRI MELALUI PENGEMBANGAN â€œTEKNOLOGI TEPAT GUNA BUDI DAYA KECAMBAHâ€: (Suatu Program Pengembangan Petani Perkotaan Berbasis Usaha Kecil dan Menengah / UKM) - wijayanti, punik mumpuni; Hadi, Daryanto Hadi (PRIMA EKONOMIKA, 2019)
Our country, indonesia this is including rich country, especially is rich in natural resources which is not possessed by another country .But unfortunately the use of indonesian natural resources not maximum .We know together that from year to year, problems the unemployment rate in indonesia also continues. There has been no solution that formula for reduce the high unemployment until now. Procurement the field working it is not enough to reduce unemployment in our country. It can be said that the number of job seekers in urban areas higher than in rural areas, and on the basis of sex so job seekers women have number equal to job seekers man .Based on the data SP2010, the open unemployment rate in indonesia is 2.6 percent. On the basis of sex, male tpt is 2,0 percent, while women tpt is 3.6 percent. Based on regional, the unemployment rate in urban 3.6 percent while in rural areas at 1.7 percent. So that it can be said that female open unemployment rate higher than open unemployment rate mani, and based on the region the open unemployment rate urban higher than open unemployment rate rural.A design study was conducted research using action with the total sample 30 women in pujokusuman for cultivation bean sprouts. To cultivation using was technology bean sprouts spring automatisasi i have designed more efficient than used a traditional.Benefits and the results of cultivation bean sprouts are ( 1 ) farmers urban profit financial clean of IDR 2.700.000 per month, ( 2 ) a rise of nutrition family for the. As for for reprocessing after harvest into flour wheat, obtained of biscuit products which worth nutrition high for the children and toddlers.Keyword: bean sprouts, cultivation, was technology precisely in order to.